Descripción comparativa entre los Gestores de Contenidos JOOMLA y DRUPAL, para la implementación de un sitio web de la Carrera de Ciencias Sociales en la Facultad de Ciencias de la Educación Humanas y Tecnologías de la Universidad Nacional de Chimborazo - González Polo, Walter Enrique (2016)
The School of Social Science, faculty of Education, Humanities and Technologies at the University of Chimborazo, lacked of a computer communication space for authorities, teachers, students and other members of the educational community to socialize different scientific, cultural, social and sports events, as well as institutional agreements or some other relevant news. Thus, the need to develop this study whit a descriptive level aroused based on comparative causal studies that sought to determine the implementation of a web site for the School of Social Science, which turns out to be a valuable contribution to the evaluation process and the institutional accreditation. To verify the characteristics of CMS JOOMLA and DRUPAL, comparison tables that were utilized presented items like satisfaction, strengths, weaknesses, security, ease of use advantages and disadvantage. The comparative study found that JOOMLA is the most suitable way to achieve 82.42% of the established parameters. This research was carried out during the implementation process of a website and published as the domain called “cienciassociales.unach.edu.ec” in the official website of the University of Chimborazo.